A Hidden Aspect of Physical Child Abuse: A Case of Voyeurism. Issue 1 (1st January 2019) - Vadysinghe, Amal Nishantha; Dassanayake, Prasanna Bandara; Mudiyanselage Kasun Dhananjaya Katugaha, Bandaranayake Herath
ABSTRACT: Child abuse is an area in forensic medicine where detailed information is required for proper management. The authors present a case of physical child abuse, inflicted by the guardian to control voyeuristic behavior of the child. This has not been reported previously. An 11-year-old female, from a poor socioeconomic background, was brought by the police for clinical forensic examination, with a history of having been assaulted at home. The class teacher had noted limping and lack of concentration causing poor performance in studies, which was of recent onset. Assessment revealed that the child was physically abused by her stepfather. Deep inquiry revealed the reason for assault as punishment for watching parents engage in sexual intercourse (voyeurism), which the child did repeatedly, in spite of severe warning. This case highlights the importance of delving deep into the background of the child to identify rare psychological disorders and to prevent injustice to alleged perpetrators and victims.